Sustainable economic development : perspectives from political economy and economics pluralism - Meramveliotakis, Giorgos; Manioudis, Manolis (Routledge Frontiers of Political Economy, 2025)
Drawing on political economy and economic pluralism, this book explores issues in sustainable economic development from a macro perspective. In contrast to the vast majority of studies on contemporary development problems, which are focused on micro-level theory, method, and policy, this volume brings together both heterodox and mainstream perspectives. The international cast of contributors thus brings a pluralistic approach to core contemporary topics including digital transformation, climate change, degrowth and the effects of the pandemic crisis. Methods range from frameworks used to analyse public policy and institutional change, to modes of analyses including historically grounded narratives and conceptualisations of grand theories. Each chapter surveys the origins, development, key features, applications, and frontiers of a particular viewpoint, framework, or mode of analysis. This book makes a vital contribution to the literature on economic development, sustainable development, capitalism, and sustainability more broadly.